New Media, New Practices: Reframing Scholarly Communication for the 21st Century - Caidi, Nadia; Moore, Gale; Chan, Leslie; Arsenault, Clément (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Scholarly communication plays a critical role not only in the dissemination of knowledge, but also in the production of scholarly careers and the reproduction of scholarly communities. In the digital era innovative and diverse forms of scholarship are emerging that present opportunities for leadership and research. How might CAIS/ACSI respond? Les communications savantes jouent un rôle essentiel non seulement dans la diffusion de la connaissance, mais également dans la production de carrières universitaire et dans le développement de la communauté de la recherche. À l’ère numérique, des formes novatrices et diverses proposent de nouvelles occasions de leadership et de recherche. Comment s’ajustera l’ACSI/CAIS? Moderator: Nadia Caidi Panelists: Gale Moore, Senior Fellow & former Director KMDI (2003-2008), Member, Graduate faculty, Dept. of Sociology, Member, Tri-campus Working Group on Scholarly Communication, University of Toronto Leslie Chan, Senior Lecturer and Program Supervisor, International Development Studies, Director, Bioline International, University of Toronto Scarborough Clément Arsenault, Associate Professor and Director, École de bibliothéconomie et des sciences de l’information, Université de Montréal, Editor-in-chief, CJILS/RCSIB